Polarized laser scattering detection of subsurface damage of quartz glass induced by grinding - Shi, Fangyuan; Qiao, Guowen; Lv, Qixin; Bai, Qian (Frontiers in Materials, 2023)
Subsurface damage (SSD) is inevitably generated during the grinding process of quartz glass. It is significant to develop the SSD detection method for the optimization of the subsequent processing parameters. This paper proposes a nondestructive detection method for detecting SSD in ground quartz glass based on polarized laser scattering (PLS). Ground samples of quartz glass were prepared with different abrasive particle sizes. A PLS system was built to detect SSD in these samples. The finite-difference time-domain (FDTD) method was used to simulate the laser scattering process at the SSD. It is concluded that the PLS system can effectively detect SSD in the ground quartz glass.